Checklist of longicorn beetles (Coleoptera, Cerambycidae) of Omsk Region (Russia) - Saikina, Sofya M.; Knyazev, Svyatoslav A.; Ponomarev, Konstantin B.; Teploukhov, Vladimir Yu.; Kosheleva, Tatyana F.; Dubatolov, Vladimir V. (Acta Biologica Sibirica, 2022)
An annotated check-list of the longicorn beetles of Omsk Region is given. The list based on literature data and collecting materials of authors. 41 species are new to the fauna of Omsk Region.